MRI monitoring of USPIO-labeled BMSCs combined with alginate scaffold for cartilage defect repair - Shanyu Lu; Shanyu Lu; Zhenyu Liu; Zhenyu Liu; Meiling Qi; Meiling Qi; Haocheng Zhen; Jing Luo; Yingchao Wang; Yingchao Wang; Le Chang; Le Chang; et al. (Frontiers in Bioengineering and Biotechnology)
ObjectiveThis study aimed to evaluate the effectiveness of bone marrow mesenchymal stem cells (BMSCs) combined with sodium alginate scaffolds in repairing knee cartilage defects in New Zealand rabbits. Additionally, it assessed the potential of functional magnetic resonance imaging (fMRI) for non-invasive monitoring of the dynamic repair process.MethodsRabbits were randomly divided into four groups: Group A (control), Group B (sodium alginate scaffold), Group C (BMSCs-sodium alginate scaffold), and Group D (USPIO-labeled BMSCs-sodium alginate scaffold). A cartilage defect model was created, and the respective materials were implanted into the defect regions. T2 mapping MRI was performed at weeks 1, 2, and 4 post-surgery to evaluate the repair process, followed by histological analysis to confirm the outcomes.ResultsBMSCs significantly promoted cartilage defect repair and accelerated the degradation of sodium alginate scaffolds. Macroscopic and histological evaluations revealed repair tissue formation in Groups C and D by week 1, with most defect regions filled with new cartilage by week 4. T2 mapping analysis showed a gradual decline in T2 values in Group B, a more pronounced decrease in Group C, and consistently lower T2 values in Group D compared to Group C, with a slow upward trend over time.ConclusionThis study demonstrated that BMSCs exhibit significant regenerative potential for cartilage defect repair. USPIO labeling enables non-invasive, dynamic monitoring of the repair process without adverse effects on cell viability or differentiation. These findings provide experimental evidence supporting the application of BMSCs combined with magnetic labeling technology in cartilage regeneration.